Faster balls increase the probability of scoring a goal in female and male elite goalball - Márcio Pereira Morato; Rafael Pombo Menezes; Sofia Fonseca; Otávio Luis Piva da Cunha Furtado
Abstract We sought to investigate the influence of ball time, ball trajectory and ball type on the probability of scoring a goal in female and male elite goalball. We also aimed to categorize throw ball time, taking into consideration ball trajectory and ball type. Systematic video analysis of 1341 male and 1304 female throws was performed on 20 randomly selected matches from the Paralympic Games. In both genders, reducing ball time was associated with an increased probability of scoring a goal, while there was no association for ball trajectories or ball types. The proposed ball time categories are thought to be a useful tool for coaches and sport scientists, as it provides reference values on how fast a ball moves regarding different ball trajectories and ball types for each gender.